Ballistic stretching increases flexibility and acute vertical jump height when combined with basketball activity - Woolstenhulme, M. T.; Griffith, C. M.; Woolstenhulme, E. M.; Parcell, A. C. (The Journal of Strength and Conditioning Research, 2006)
Stretching is often included as part of a warm-up procedure for basketball activity. However, the efficacy of stretching with respect to sport performance has come into question. We determined the effects of 4 different warm-up protocols followed by 20 minutes of basketball activity on flexibility and vertical jump height. Subjects participated in 6 weeks (2 times per week) of warm-up and basketball activity. The warm-up groups participated in ballistic stretching, static stretching, sprinting, or basketball shooting (control group). We asked 3 questions. First, what effect does 6 weeks of warm-up exercise and basketball play have on both flexibility and vertical jump height? We measured sit and reach and vertical jump height before (week -1) and after (week 7) the 6 weeks. Flexibility increased for the ballistic, static, and sprint groups compared to the control group (p < 0.0001), while vertical jump height did not change for any of the groups. Our second question was what is the acute effect of each warm-up on vertical jump height? We measured vertical jump immediately after the warm-up on 4 separate occasions during the 6 weeks (at weeks 0, 2, 4, and 6). Vertical jump height was not different for any group. Finally, our third question was what is the acute effect of each warm-up on vertical jump height following 20 minutes of basketball play? We measured vertical jump height immediately following 20 minutes of basketball play at weeks 0, 2, 4, and 6. Only the ballistic stretching group demonstrated an acute increase in vertical jump 20 minutes after basketball play (p < 0.05). Coaches should consider using ballistic stretching as a warm-up for basketball play, as it is beneficial to vertical jump performance.